2015
DOI: 10.1155/2015/959138
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotics to Control Aflatoxin Production in Peanut Grains

Abstract: Probiotic microorganisms (Saccharomyces cerevisiae var. boulardii, S. cerevisiae UFMG 905, and Lactobacillus delbrueckii UFV H2b20) were evaluated as biological control agents to reduce aflatoxin and spore production by Aspergillus parasiticus IMI 242695 in peanut. Suspensions containing the probiotics alone or in combinations were tested by sprinkling on the grains followed by incubation for seven days at 25°C. All probiotic microorganisms, in live and inactivated forms, significantly reduced A. parasiticus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…(Basappa & Shantha, 1996;Oluwafemi, Kumar, Bandyopadhyay, Ogunbanwo, & Ayanwande, 2010). On the other hand, it was found that the bacterial detoxification of mycotoxins is more preferable than the other methods; owing to the short time, it takes for elimination and the nonpigments production (Da Silva et al, 2015;Laciakova, Cicooova, Mate, & Laciak, 2008). It was reported that probiotics are important for reduction of serum cholesterol, acting as antagonist against food-borne and many others pathogenic fungi which infect the human intestine (Kaur, Chopra, & Saini, 2002;Zerehpoosh & Darsanaki, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Basappa & Shantha, 1996;Oluwafemi, Kumar, Bandyopadhyay, Ogunbanwo, & Ayanwande, 2010). On the other hand, it was found that the bacterial detoxification of mycotoxins is more preferable than the other methods; owing to the short time, it takes for elimination and the nonpigments production (Da Silva et al, 2015;Laciakova, Cicooova, Mate, & Laciak, 2008). It was reported that probiotics are important for reduction of serum cholesterol, acting as antagonist against food-borne and many others pathogenic fungi which infect the human intestine (Kaur, Chopra, & Saini, 2002;Zerehpoosh & Darsanaki, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Da Silva et al . () showed an effective biological control capacity of probiotic strains of S. boulardii (CNCM‐17) because they significantly reduced spore production of Aspergillus parasiticus in peanuts. It was determined that all probiotics inhibited sporulation of the molds, obtaining better results with living cells.…”
Section: Nutritional and Nutraceutical Implications Of S Boulardii Imentioning
confidence: 99%
“…Silva et al . () reported that S. cerevisiae UFMG905 caused a significant reduction in aflatoxin production by A . parasiticus .…”
Section: Resultsmentioning
confidence: 99%
“…This significant decrease in AF levels in cocultures with yeast appears to be related to the inhibition of A. flavus growth. Silva et al (2015) reported that S. cerevisiae UFMG905 caused a significant reduction in aflatoxin production by A. parasiticus. These results suggest that the biological control with selected yeasts could reduce not only the spore dispersion, but also the aflatoxins production by the spoilage fungi.…”
Section: S Cerevisiae Mode Of Action Under Semmentioning
confidence: 99%